Cyber-vigilance and digital trust : cyber security in the era of cloud computing and IoT - Tounsi, Wiem (Networks and telecommunications series., 2019)
Reviewing recent advances in cyber threat intelligence, trust management and risk analysis, this book gives a formal and technical approach based on a data tainting mechanism to avoid data leakage in Android systems. --